Late holocene coastal plain stratigraphy and sea-level history at Hanalei, Kauai, Hawaiian islands - Calhoun, R. S.; Fletcher, C. H. (Quaternary Research, 1996)
Fluvial, marine, and mixed fluvial-marine deposition on the coastal plain of Hanalei Bay on the north shore of Kauai, Hawaii, records a middle- to late-Holocene fall of relative sea level. Radiocarbon dating of the regression boundary preserved in the stratigraphy of the coastal plain documents a seaward shift of the shoreline beginning at least 4800-4580 cal yr B.P. and continuing until at least 2160-1940 cal yr B.P. Marine sands stranded in the backshore and coastal plain environment are buried by fluvial floodplain and channel sands, silts, and muds. In places, erosion at the regression contact exposed older marine sands thus increasing the hiatus at the regression disconformity, The shoreline regression is best explained as the result of a fall in relative sea level. The age and elevation of the cored regression boundary at sites that have not been influenced by erosion are consistent with a middle-to late-Holocene highstand of relative sea level as predicted by geophysical models of whole Earth deformation related to deglaciation. (C) 1996 University of Washington.
Uf728Times Cited:21Cited References Count:35